(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article presents a comprehensive comparative analysis of franchising models as a strategic framework for international expansion, focusing on the distinct approaches of European and American corporations. The analysis reveals a fundamental dichotomy: American franchising prioritizes rapid scalability, brand standardization, and a regulatory framework centered on pre-contractual transparency (FTC Rule). In contrast, the European model emphasizes cultural adaptation, long-term sustainability, regulatory diversity, and often a more collaborative franchisor-franchisee relationship, guided by a voluntary European Code of Ethics. The article identifies key success factors, including the balance between standardization and localization, the critical role of franchisor support, and the impact of digital transformation.